Satisfaction on clinical learning environment among nursing students of selected medical colleges of Chitwan, Nepal - Dhakal, Prativa; Thapa, Taniya (Journal of Chitwan Medical College, 2020)
Background: Clinical learning environment includes everything that surrounds students and is extremely beneficial in stimulating their critical thinking and affects their professional development via focus on clinical judgment and decision–making in the clinical setting. This study aims to assess the level of satisfaction on clinical learning environment among nursing students of selected medical colleges of Chitwan, Nepal. Methods: Descriptive, cross sectional study design was used to assess the satisfaction on clinical learning environment among nursing students of selected medical colleges of Chitwan. Standard tool (CLES + T scale) was administered among 242 nursing students. Data was entered in IBM Statistical Package for Social Science (SPSS) version 20.0 and was further analyzed by using descriptive statistics and inferential statistics. Results: Just more than half of the nursing students were highly satisfied (51.2%) with the clinical learning environment. The level of satisfaction among nursing students was found statistically significant with year of study and type of ward of latest clinical placement with p value <0.05. Conclusions: Nearly half of the students are still not highly satisfied towards their clinical learning environment, therefore improvement in its quality needs proper planning, implementation and supervision that too in government hospital settings.